Exploring the Experiences of Women with OCD in Workplace: A Qualitative Study - Khazaeipul, Suzan; Teymouri, Mitra; Alimardani, Hengame; Bagheri, Raziyeh; Ghorbanzadeh Korani, Zeinab (Applied Family Therapy Journal (AFTJ), 2024)
Obsessive-Compulsive Disorder (OCD) in women remains underexplored in occupational contexts, despite its significant impact on functioning and well-being. This study aims to explore the lived experiences of women with OCD in the workplace. Utilizing a qualitative, phenomenological approach, the research was conducted in Tehran, Iran. Semi-structured interviews were conducted with 19 employed women formally diagnosed with OCD across diverse professional sectors. Sampling continued until theoretical saturation was achieved. Interview transcripts were analyzed thematically using NVivo software. Four core themes emerged: Workplace Challenges, Coping Mechanisms, Perceived Organizational Support, and Effects on Professional Identity. Participants reported challenges such as intrusive thoughts during tasks, compulsive checking behaviors, time-consuming rituals, perfectionism, and heightened anxiety in high-pressure environments. Coping mechanisms included cognitive-behavioral strategies, medication adherence, mindfulness practices, supportive routines, and seeking social or therapeutic support. Perceptions of organizational support ranged widely, with positive experiences linked to empathetic supervisors, mental health accommodations, and flexible work structures. OCD also influenced participants’ professional identity, contributing to both self-doubt and the recognition of strengths such as attention to detail, reliability, and conscientiousness. These findings underscore the necessity for workplace awareness, mental health inclusivity, and targeted interventions to support women with OCD. Creating supportive and stigma-free environments can enhance these employees’ job satisfaction, engagement, and career development